Causal Modelling of Head Teachers' Leadership Behaviour and Administrative Effectiveness in Public Basic School: Validation of the Measurement Instrument. - Adewale, Awodiji Omotayo; Adekunle, Ayanwale Musa (Pertanika Journal of Social Sciences & Humanities, 2023)
Educational leadership behaviour and effectiveness instruments available in the literature are primarily outside the African continent. Educational leadership researchers do not consider the cultural context in adopting scale. In Sahara-Africa, where Nigeria is located, researchers have scientific and ethical questions on the validity of the instruments used for data collection. Experience showed that researchers in Sahara Africa tousled for an instrument to conduct their study in leadership and management, resulting in a self-designed instrument without adequate validation. The study, therefore, validated the measurement scale on head teachers' behaviour and administrative effectiveness in public primary schools. A non-experimental design was adopted for the scale development. Parallel analysis was used to establish factors of the scales and construct validity and reliability with the aid of R-programming and Partial Least Square Structural Equation Modelling. The results showed that leadership behaviour has three components (directive, supportive, and consultative) with 29 items. It was in line with the path-goal and situation theories underpinning this study. Also, the average variance extracted for all the components was above the 0.50 cut-off, HTMT values were below 0.90, and composite reliabilities were above 0.70, respectively. Thus, the scales were valid and reliable to use by researchers interested in this area.